FACTORS RELATED TO NURSES' PERFORMANCE IN REPORTING PATIENT SAFETY INCIDENTS AT PERMATA HATI HOSPITAL DURI IN 2025 - Arba’a, Nurhamni; Lita, Lita; Kiswanto, Kiswanto; Herniwanti, Herniwanti; Jepisah, Doni (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Patient safety stands as a vital benchmark of healthcare quality, yet reporting incidents remains a challenge influenced by multiple human and organizational factors. This study explores the elements that shape nurses’ performance in reporting patient safety incidents at Permata Hati Duri Hospital in 2025. Using a quantitative analytical observational approach with a cross-sectional design, the research involved 85 inpatient nurses. Data were analyzed through univariate, bivariate (Fisher’s Exact test), and multivariate (logistic regression) techniques. Most participants were young adults aged 20–30 years (32.9%), predominantly female (91.8%), highly educated (84.7% D4/S1/Nursing), and experienced (80.0% with 6–>10 years). Findings revealed that most nurses demonstrated strong perceptions, positive attitudes, high motivation, and favorable views of leadership. Although bivariate analysis showed no significant association between independent variables and incident reporting, multivariate results indicated that work experience played the most dominant role (OR = 3.821; 95% CI = 0.010–1.025). The study concludes that enhancing reporting behavior requires consistent training, improved digital systems, and a reinforced culture of safety across all levels of hospital practice.